Regulating Blockchain-Enabled Green Finance: A Comparative Analysis of Emerging vs. Developed Markets - Munir, Ayesha; Barrow, Aisha (JIAN (Jurnal Ilmiah Administrasi Negara), 2025)
The potential for blockchain technology to revolutionize green finance is its capacity for enhanced transparency, efficiency, and accountability for sustainable investments. However, the adoption is hindered by the heterogeneity of regulatory frameworks for various economies. This paper undertakes comparative analysis of regulations around blockchain-facilitated green finance for emerging and developed economies. It examines the main regulatory hurdles, differences in the structure of policies, and implications for the mandates for complying with blockchain-led sustainable finance activities. Based on the analysis through the lens of European Union, United States, Indonesia, Pakistan, and UAE, this study sketches best practice and hurdles for the adoption of blockchain for the adoption of green finance. Additionally, the study reflects upon the impact of the government and financial institutions towards the adoption of blockchain for the cases of ESG investments, green bonds, and the carbon market. Suggestive policies for resolving regulatory disparities and global harmonization for the adoption of blockchain for sustainable finance are given.